Accurate Neurosurgery for the Establishment of the Electric Kindling Model of Epilepsy in Mice - Verónica Custodio; Jorge Acosta; Carmen Rubio; Leonardo Hernández; Javier Brito; Elisa Taddei (Journal of Investigative Surgery, 2022)
This article describes in detail the essential stereotaxic neurosurgery to develop the electric experimental kindling model in mice. To date, available literature describing the methodology of the kindling model is very poor and usually neglects many relevant details about the neurosurgery, such as the manufacture of the electrodes, accurate stereotaxic coordinates of the amygdala nuclei, and the general surgery procedures (e.g., anesthesia, postsurgical recovery, fit survival of the animal’s). The electric kindling model produces a progressive development of generalized tonic-clonic seizures, which can be assessed by electroencephalography and behavioral responses. The seizures displayed are produced by a repeated low-intensity electrical stimulation in specific regions of the brain that is achieved through the previous implantation of electrodes. In this study, the aim was to implant the electrodes in basolateral amygdaloid nucleus (BLA). In order to successfully establish the kindling experimental model, neurosurgery to place the electrodes is an essential step to develop the epileptogenic phenomenon. It crucial that the surgery is carried out with exceptional exactitude, because in that way the experimental model represents an accurate and valid tool to study and understand epilepsy and the results obtained can be used to develop further strategies in epilepsy clinical research.